ANALISIS STRATEGI GURU DALAM MENANAMKAN NILAI PENDIDIKAN KARAKTER PADA SISWA KELAS IV DI SD NEGERI 05 PALEMBANG - Nurijah Ratimawadah; Sukardi; Aldora Pratama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the use of teacher strategies in instilling character education values in grade IV students at SD Negeri 05 Palembang. The method used in this research is qualitative method with descriptive approach. The source of data in this study was from class IV A and IV B teachers. The data collection techniques of this research include: observation, interview, and documentation. Research results 1) The Teacher's Strategy in Instilling Religious Character Values in Class IV Students at SD Negeri 05 Palembang is doing prayer activities before and after learning, reminding children to always be grateful to God and always giving direct examples as well as understanding. getting used to 5 S (smile, greeting, greeting, polite and courteous). 2) Teachers' Strategies in Instilling Tolerance Character Values in Grade IV Students at SD Negeri 05 Palembang, namely giving examples, encouraging students to always remember good things when in class and outside the classroom, daily routine activities. 3) Teachers' Strategies in Instilling Disciplinary Character Values in Class IV Students at SD Negeri 05 Palembang are giving punishment, exemplary/example, and doing habituation. 4) Teachers' Strategies in Instilling Democratic Character Values in Class IV Students at SD Negeri 05 Palembang are giving children freedom, implementing group-based learning, conducting flag ceremony activities every Monday. 5) Teachers' Strategies in Instilling Environmental Care Character Values in Class IV Students at SD Negeri 05 Palembang are giving examples/examples and habituating students.